(untitled) (Journal of Social Sciences Review, 2025)
It is interesting to note that the British society, which bears a symbol of secularism, owns an uncodified constitution that possesses significant religious characteristics, pertaining not only to a particular religion (Christianity) but also to a particular denomination (protestant). These constitutionally evolved religious features are generally neglected in the British constitutional discourse and debates for the reason that the British constitution is presumed to be a secular constitution whereas the facts state otherwise as it bears several significant historical statutes which mark its religious relevance. Moreover, such a presumed impression of constitutional secularism of the UK tends to be generally misleading various circles and quarters of the Pakistani society; which may potentially result into a motivation for socio-political campaigns in Pakistan for the same pursuit based on the misunderstood constitutional position of the UK. Thus, this article attempts to highlight those significant religious documents, Acts and conventions which provide ample evidence that the UK constitution is not a secular constitution for several reasons such as its historical recognition for deep-rooted nexus between the constitutional monarchy, Parliament and Established Church of England and Scotland. In addition, the legal framework of the UK also contains strong and significant religious representations in all the three military forces, state-funded schools and prisons across the UK.